2021
DOI: 10.4274/jtgga.galenos.2021.2020.0176
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors with neonatal near miss in twin pregnancies in a public referral maternity unit in Brazil

Abstract: Objective: The aim was to analyze the factors associated with neonatal near miss (NNM) in twin pregnancies in a public referral maternity unit in Brazil. Material and Methods: This retrospective, cross-sectional study included 697 twin newborns. Cases of fetal and neonatal deaths were excluded. Neonates were divided into those meeting NNM criteria (5 min Apgar score <7, birth weight <1,500 g, gestational age at delivery <32 weeks, use of mechanical ventilation or congen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
5
0
3
Order By: Relevance
“…In the period studied, in Cuiabá-MT-Brazil a NMR of 7.5/1.000 NB and a NNMR of 22.8/1,000 NB, resulting in 3.04 cases of NNM for each neonatal death, resulting in data similar to those of a study developed in a Fortaleza-CE maternity hospital, which identified 2.2 cases of NNM for each death. 14 A study carried out in the cities of São Paulo (SP), Rio de Janeiro (RJ) and Niterói (RJ), using almost the same pragmatic criteria of this research, excluding congenital anomaly and mechanical ventilation, found an NNMR of 17.2/1.000 NB. 4 On the other hand, a research developed in 191 Brazilian cities 10 and another carried out in Joinville-SC, 11 which used the same criteria of NNM in this study, with the addition of mechanical ventilation, obtained respectively the NNMR of 39.2/1.000 live births and a NMR of 11.1/1.000 live births, resulting in 3.5 cases of NNM for each death 10 and NNMR of 33/1.000 live births and a NMR of 4.5/1.000 live births, so for each 7.3 cases of NNM there was one death.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In the period studied, in Cuiabá-MT-Brazil a NMR of 7.5/1.000 NB and a NNMR of 22.8/1,000 NB, resulting in 3.04 cases of NNM for each neonatal death, resulting in data similar to those of a study developed in a Fortaleza-CE maternity hospital, which identified 2.2 cases of NNM for each death. 14 A study carried out in the cities of São Paulo (SP), Rio de Janeiro (RJ) and Niterói (RJ), using almost the same pragmatic criteria of this research, excluding congenital anomaly and mechanical ventilation, found an NNMR of 17.2/1.000 NB. 4 On the other hand, a research developed in 191 Brazilian cities 10 and another carried out in Joinville-SC, 11 which used the same criteria of NNM in this study, with the addition of mechanical ventilation, obtained respectively the NNMR of 39.2/1.000 live births and a NMR of 11.1/1.000 live births, resulting in 3.5 cases of NNM for each death 10 and NNMR of 33/1.000 live births and a NMR of 4.5/1.000 live births, so for each 7.3 cases of NNM there was one death.…”
Section: Discussionmentioning
confidence: 62%
“…28 Few researches have investigated the relationship between the type of pregnancy (single, double, triple or more) and the NNM 11,25-27 and revealed a higher risk of multiple pregnancy and the outcome (NNM), which was also observed in the findings of this study. It is also noteworthy that this variable is considered a risk factor for neonatal mortality 21,25 and the worst results for severe neonatal morbidity, 14 being important that prenatal care services monitor high-risk pregnancies, providing appropriate information to multiparous women about the consequences and risks of multiparity. 27 As for the number of live children in previous pregnancies and their relationship with NNM, 14 there is still no scientific evidence, although this study identified an association of NNM with the mother having no or one live-born child in a previous pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found a relationship between advanced maternal age and neonatal near-miss in nulliparous and multiparous women 6 . In addition, it was stated that neonatal near-miss risk in twins was associated with parity, an early gestational week, and intrauterine growth restriction 18 . Although maternal age affects the prevalence of twins, it does not appear to affect twin pregnancy outcomes; furthermore, the preterm birth risk was higher among younger mothers 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The rate of twin pregnancies in all pregnancies is approximately 1-2% 1 . In multiple pregnancies, an increase has been seen in recent years, and the reason for this is the development of reproductive techniques and advanced maternal age 2 . The increase in the frequency of multiple pregnancies is accompanied by negativities related to maternal and fetus health.…”
Section: Introductionmentioning
confidence: 99%